Kentucky Equestrians: Defining Socioeconomic Contexts for Extension Programming - Kimberly I. Tumlin; Karin Pekarchik; Steven Claas ([TEST] Journal of Extension, 2021)
Understanding relationships between demographic and economic factors and equestrian participation could improve horse program design. We implemented an online survey that characterized associations of participation in equine activities, socioeconomic factors, and economic factors with age. Seventy-five percent of respondents ride, and 34% are recreational, non-competitive participants. Respondents were mostly female, and many participate in the sport throughout life. Many respondents indicated they overspent on equestrian activities. Horse programs should incorporate information and activities that address issues unique to females, should develop skills required by amateur or recreational riders, and should incorporate information on financial wellness.
Keywords: socioeconomic status; equestrians; economic factors; age contexts; program